LPA Promotes T Cell Recruitment through Synthesis of CXCL13 - Weili Hui; Chenqi Zhao; Sylvain G. Bourgoin (Mediators of Inflammation)
Lysophosphatidic acid (LPA) is a bioactive phospholipid playing an important role in various inflammatory diseases by inducing expression and secretion of many inflammatory cytokines/chemokines. Here we report in a murine air pouch model of inflammation that LPA induced CXCL13 secretion in a time-dependent manner and with exacerbation of the response when LPA was administered after a pretreatment with TNF-α, a key inflammatory cytokine. LPA mediates recruitment of leukocytes, including that of CD3+ cells into unprimed and TNF-α-primed air pouches. CXCL13 neutralization using a blocking antibody injected into air pouches prior to administration of LPA into TNF-α-primed air pouches decreased CD3+ cell influx. Our data highlight that LPA-mediated CXCL13 secretion plays a role in T cell recruitment and participates in regulation of the inflammatory response.